Q: -3 plus y equals 17 plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

10x + 17 = 4x - 16x = -18x = -3

Basically, 3/3 equals 1. So 1 plus 1/16 is 1 and 1/16. Or 17/16.

Multiply the bottom equation by -1

17.

42

Related questions

10x + 17 = 4x - 16x = -18x = -3

Basically, 3/3 equals 1. So 1 plus 1/16 is 1 and 1/16. Or 17/16.

Multiply the bottom equation by -1

17.

3 plus 1 plus 4 equals 8

1.66666666666666666667 because 3 plus 1 plus 1 equals 5 and 5 divided by 3 equals 1.6666666666666666666.7.

42

21 Uhm, no, 17 actually...

6+1 equals 7. Plus 3 equals 10. Plus 4 equals 14.

Unless I'm misunderstanding the question, 1 plus 1 plus 1 equals 3 CAN be written as a multiplication sentence: 1 times 3 equals 3.

if 'g' = minus 3 then 20 + -3 = 17 17 + -3 = 14

a - 3 + 17 = 10 Therefore, a - 3 = -7 a = -4